Porcine blood cell and brain tissue energy metabolism: Effects of “early life stress” - Münz, Franziska; Wolfschmitt, Eva-Maria; Zink, Fabian; Abele, Nadja; Hogg, Melanie; Hoffmann, Andrea; Gröger, Michael; Calzia, Enrico; Waller, Christiane; Radermacher, Peter; Merz, Tamara (Frontiers in Molecular Biosciences, 2023)
Background: Early Life Stress (ELS) may exert long-lasting biological effects, e.g., on PBMC energy metabolism and mitochondrial respiration. Data on its effect on brain tissue mitochondrial respiration is scarce, and it is unclear whether blood cell mitochondrial activity mirrors that of brain tissue. This study investigated blood immune cell and brain tissue mitochondrial respiratory activity in a porcine ELS model. Methods: This prospective randomized, controlled, animal investigation comprised 12 German Large White swine of either sex, which were weaned at PND (postnatal day) 28–35 (control) or PND21 (ELS). At 20–24 weeks, animals were anesthetized, mechanically ventilated and surgically instrumented. We determined serum hormone, cytokine, and “brain injury marker” levels, superoxide anion (O2•¯) formation and mitochondrial respiration in isolated immune cells and immediate post mortem frontal cortex brain tissue. Results: ELS animals presented with higher glucose levels, lower mean arterial pressure. Most determined serum factors did not differ. In male controls, TNFα and IL-10 levels were both higher than in female controls as well as, no matter the gender in ELS animals. MAP-2, GFAP, and NSE were also higher in male controls than in the other three groups. Neither PBMC routine respiration and brain tissue oxidative phosphorylation nor maximal electron transfer capacity in the uncoupled state (ETC) showed any difference between ELS and controls. There was no significant relation between brain tissue and PBMC, ETC, or brain tissue, ETC, and PBMC bioenergetic health index. Whole blood O2•¯ concentrations and PBMC O2•¯ production were comparable between groups. However, granulocyte O2•¯ production after stimulation with E. coli was lower in the ELS group, and this effect was sex-specific: increased O2•¯ production increased upon stimulation in all control animals, which was abolished in the female ELS swine. Conclusion: This study provides evidence that ELS i) may, gender-specifically, affect the immune response to general anesthesia as well as O2•¯ radical production at sexual maturity, ii) has limited effects on brain and peripheral blood immune cell mitochondrial respiratory activity, and iii) mitochondrial respiratory activity of peripheral blood immune cells and brain tissue do not correlate.